Measuring morbidity associated with urinary schistosomiasis: assessing levels of excreted urine albumin and urinary tract pathologies. - José C Sousa-Figueiredo; María-Gloria Basáñez; I Simba Khamis; Amadou Garba; David Rollinson; J Russell Stothard (PLoS Neglected Tropical Diseases)
Background Urinary schistosomiasis is responsible for a variety of debilitating conditions; foremost perhaps are urinary tract pathologies (UTPs). Although portable ultrasonography can be used to detect UTPs visually, there is still a need for rapid morbidity assessment (henceforth referred to as RaMA) tools that can be deployed in the field during implementation, monitoring and evaluation of control programmes. We therefore aimed to determine associations between excreted urine-albumin, as measured using a HemoCue photometer, and UTPs, as detected by ultrasonography, in children and adults from an urinary schistosomiasis endemic area in Zanzibar. Methodology/principal findings In a survey of 140 school-children of both sexes (aged 9 to 15 yr) and 47 adult males (> or =16 yr) on the island of Unguja, the prevalence of egg-patent urinary schistosomiasis was 36.4% (CI(95) 28.5-45.0%) and 46.8% (CI(95) 32.1-61.9%) (P = 0.14), and that of UTPs was 39.4% (CI(95) 31.0-48.3%) and 64.4% (CI(95) 48.8-78.1%) (P = 0.006), respectively. In school-children, raised urine-albumin concentrations (>40 mg/L) were associated, albeit non-significantly, with prevalence of infection (OR = 3.1, P = 0.070), but more specifically and significantly with the prevalence of micro-haematuria (OR = 76.7, P<0.0001). In adults, elevated urine-albumin excretion was associated with UTPs, particularly lesions of the bladder wall (OR = 8.4, P = 0.013). Albuminuria showed promising diagnostic performance, especially in school-aged children with sensitivity of 63.3% and specificity of 83.1% at detecting lower UTPs, i.e. bladder-wall lesions (ultrasonography as 'gold standard'). Conclusion/significance This study indicates that albuminuria assays could be used as a RaMA tool for monitoring UTP prevalence during control programmes, as well as a tool for selecting those with more chronic bladder-wall lesions without resorting to ultrasonography.